A case of abdominal tuberculosis diagnosed by fine needle aspiration cytology (FNAC) of mesenteric lymph node - Rai, Bijendra Kumar; Kafle, SU; Sundas, A (Health Renaissance, 2017)
Background: The modes of presentation of abdominal tuberculosis can be vague resulting in diagnostic dilemma. Objective: To report a case of abdominal tuberculosis diagnosed by FNAC of a mesenteric lymphnode. Case: A 17-year-old boy presented in General out Patient department complaining of abdominal pain, abdominal distension, and low grade fever, anorexia and weight loss for 2 months. The examination revealed pallor, low body weight, doughing of abdomen and multiple palpable painless, slightly mobile abdominal lymph nodes. The ultrasonography (USG) guided fine needle aspiration cytology (FNAC) of a mesenteric lymphnode showed caseating necrosis suggestive of tuberculosis. The erythrocytes sedimentation rate (ESR) was raised. Conclusion: The abdominal tuberculosis can present with abdominal pain and abdominal distension associated with low grade fever, anorexia and weight loss. The diagnosis of abdominal tuberculosis can be confirmed by FNAC of the lymphnodes. Health Renaissance 2015;13(3): 177-180